Inflammasome as an early pathophysiological phenomenon of inflammation in skin diseases and other pathologies - V. V. Klimov; D. S. Zagreshenko; O. I. Urazova; A. V. Klimov; O. A. Naidina; E. Yu. Tsyplina; E. N. Kologrivova; T. V. Koshovkina; N. S. Koshkarova (Бюллетень сибирской медицины, 2023)
The review considers the molecular structure of inflammasomes, routes of inflammasome activation, appropriate downstream effects, and their association with autoinflammatory, autoimmune, neurodegenerative, and allergic diseases and malignancies with a focus on the involvement of the skin in these pathologies. Inflammasome activation is interpreted as an early pathophysiological event before the onset of inflammation, and, especially, if inflammasome dysregulation occurs. All research aspects related to the NLRP3 inflammasome are described in detail. The review also considers promising directions for therapeutic interventions in NLRP3-associated diseases.